5-Nitro-3-(2-(4-phenylthiazol-2-yl)hydrazineylidene)indolin-2-one derivatives inhibit HIV-1 replication by a multitarget mechanism of action - Corona, Angela; Meleddu, Rita; Delelis, Olivier; Subra, Frederic; Cottiglia, Filippo; Esposito, Francesca; Distinto, Simona; Maccioni, Elias; Tramontano, Enzo (Frontiers in Cellular and Infection Microbiology, 2023)
In the effort to identify and develop new HIV-1 inhibitors endowed with innovative mechanisms, we focused our attention on the possibility to target more than one viral encoded enzymatic function with a single molecule. In this respect, we have previously identified by virtual screening a new indolinone-based scaffold for dual allosteric inhibitors targeting both reverse transcriptase-associated functions: polymerase and RNase H. Pursuing with the structural optimization of these dual inhibitors, we synthesized a series of 35 new 3-[2-(4-aryl-1,3-thiazol-2-ylidene)hydrazin-1-ylidene]1-indol-2-one and 3-[3-methyl-4-arylthiazol-2-ylidene)hydrazine-1-ylidene)indolin-2-one derivatives, which maintain their dual inhibitory activity in the low micromolar range. Interestingly, compounds 1a, 3a, 10a, and 9b are able to block HIV-1 replication with EC50 < 20 µM. Mechanism of action studies showed that such compounds could block HIV-1 integrase. In particular, compound 10a is the most promising for further multitarget compound development.